CFD ANALYSIS OF OFFSHORE HAWT BASED ON WIND SPEED PROFILE AT 50 METERS ALTITUDE IN THE SOUTHERN WATERS OF UJUNG PANDANG, SOUTH SULAWESI - Sutisna, Nanang Ali; Ritonga, Yehezkiel Kusmadi (President University, 2024)
Offshore wind turbines have many advantages over onshore wind turbines, with better wind speeds, fewer spatial constraints, and decreased visual and noise effects in densely populated areas. Indonesia's onshore wind energy potential for wind speeds exceeding 4.0 m/s is 60.65 GW. Moreover, Indonesia's offshore wind energy ability for wind speeds exceeding 6.0 m/s is 94.23 GW. Consequently, wind speeds in offshore regions are more promising than onshore areas, which can notably enhance renewable electricity generation and reduce the usage of fossil fuels. This research is conducted by modeling the 3D HAWT design in 2 domains, Stationary and Rotational, which will be combined in one interface. The simulation results indicate a significant increase in turbine performance parameters with increasing wind speed. It also successfully modeled the interaction between wind flow and the turbine, as shown in the velocity contours that display higher wind speed distribution at the blade tips and in the pressure contours that show higher pressure distribution on the front side of the blades and on the side of the blades relative to the direction of rotation